HYGIENE AS RISK FACTORS FOR DIARRHEA AMONG TODDLERS IN MULYOREJO PRIMARY HEALTH CENTER, SURABAYA: Higiene Sebagai Faktor Risiko Diare Pada Balita di Puskesmas Mulyorejo, Surabaya - Merza Safaryna, Alifia; Nadilla Putri, Levi; Atoillah Isfandiari, Muhammad (Universitas Airlangga, 2024)
Background: Mulyorejo Primary Health Center (PHC) ranks 12th in Surabaya for diarrhea morbidity in toddlers, and there was one case of under-five deaths due to diarrhea in 2020. Purpose: This study aims to analyze hygiene as a risk factor for diarrhea in toddlers at Mulyorejo PHC, Surabaya. Methods: This study was conducted with a case-control design from December 2022 to October 2023. The case population was all toddlers aged 12-59 months at Mulyorejo PHC who had diarrhea at least in the last month. The control population consisted of toddlers aged 12-59 months living in the Mulyorejo PHC working area who had not experienced diarrhea for at least one month. The sample size amounted to 114, with a ratio of 1 1, using a simple random sampling technique. The independent variables were handwashing with soap (HWWS), food hygiene practices, latrine ownership, healthy latrines, feces disposal, and access to drinking water. Data were collected using questionnaires and observation. Chi-Square Test and Multiple Logistics Regression analyzed data. Results: HWWS (p=0.001), food sanitation (p=0.061), latrine ownership (p=0.032), and proper disposal of toddler feces (p=0.024) had a significant association with the incidence of diarrhea in toddlers at Mulyorejo PHC. Conclusion: Only the HWWS variable determines the incidence of diarrhea in toddlers at Mulyorejo PHC. Good handwashing habits with soap can prevent the occurrence of diarrhea in toddlers.